2001
DOI: 10.1002/1529-0131(200111)44:11<2503::aid-art430>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of matrix metalloproteinases and their inhibitors to cartilage proteoglycan and collagen turnover and inflammation as revealed by analyses of synovial fluids from patients with rheumatoid arthritis

Abstract: Objective To determine interrelationships in matrix turnover in articular cartilage and joint inflammation in rheumatoid arthritis (RA). Methods Synovial fluid was obtained from the knees of 63 RA patients; radiographs were evaluated to determine the RA stage. Concentrations of matrix metalloproteinases (MMPs), tissue inhibitors of metalloproteinases (TIMPs), the 846 epitope, and the keratan sulfate (KS) epitope of aggrecan, the C‐propeptide of cartilage type II procollagen (CPII; biosynthetic marker), the cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 32 publications
(60 reference statements)
3
46
2
Order By: Relevance
“…Although the present study was not designed to assess the complex functional interactions between proenzymes, activated MMP forms, and inhibitory TIMPs (38), the similar expression of the MMP/TIMP system in SpA and RA might suggest that it is equally involved in local disease features in both diseases. Indeed, the demonstration of MMP-9 in intravascular cells, in the vessel wall, and around the vessels, as well as the correlations between the expression of MMPs 2, 3, and 9 and the degree of vascularity in the present study suggest that the previously demonstrated involvement of these mediators in angiogenesis (39-42) also applies to inflamed synovium in SpA.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study was not designed to assess the complex functional interactions between proenzymes, activated MMP forms, and inhibitory TIMPs (38), the similar expression of the MMP/TIMP system in SpA and RA might suggest that it is equally involved in local disease features in both diseases. Indeed, the demonstration of MMP-9 in intravascular cells, in the vessel wall, and around the vessels, as well as the correlations between the expression of MMPs 2, 3, and 9 and the degree of vascularity in the present study suggest that the previously demonstrated involvement of these mediators in angiogenesis (39-42) also applies to inflamed synovium in SpA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, elevated protein and/or mRNA levels of MMP-1 and MMP-3 have been detected in synovial fluid and membrane (Gravallese et al 1991;Yoshihara et al 2000). Furthermore, the production of TIMP-1 and TIMP-2 in synovial fluid is also high in rheumatoid arthritis compared with normal synovial fluid, but not as high as MMPs (Ishiguro et al 2001). As a result of such an MMP-to-TIMP imbalance, degradation of bone and cartilage are accelerated (Burger et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…KS, an index of proteoglycan catabolism, was quantified by inhibition RIA using the monoclonal antibody AN9P1 Fab fragment, 125 Ilabeled adult human aggrecan as a tracer, and unlabeled aggrecan as the standard (2,21). The amino-terminal (TC A ) fragment cleaved by collagenase from triple-helical type II collagen includes (at its carboxy terminus) the neoepitope Col2-3/4C long mono , which was measured using a competitive inhibition monoclonal antibody-based enzyme-linked immunosorbent assay (ELISA) (7,8,23,24). All of these epitopes are present in canine articular cartilage and their extracts and in canine body fluids, as determined by immunohistochemistry (see below) and Western blotting.…”
Section: Methodsmentioning
confidence: 99%